214 Association of insurance status with the treatment and outcomes of adult patients with severe traumatic brain injury: a propensity matched analysis. (5th May 2020) - Porter, Austin; Brown, Clare; Wilkerson, Jon; Mick Tilford, J; Thomas, Kevin; Sexton, Kevin; Zohoori, Namvar; Rodriguez, Analiz
Abstract : Statement of Purpose: To determine if there is a disparity in treatment and outcomes among adult patients with a severe traumatic brain injury (TBI) based on health insurance status. Methods: Adult patients (18+ years old) with a severe isolated TBI were identified in the National Trauma Data Bank (2007–2014). Isolated TBI was defined as a head Abbreviated Injury Scale (AIS) score of 3+, excluding patients with another regional AIS of 3+. Procedure codes were used to identify two classifications of treatment: cranial procedures (craniotomy or craniectomy) and monitoring (external ventricular draining or intracranial pressure monitoring). Patient outcomes were determined using discharge disposition. Patients were propensity score matched using demographics and condition on admission to determine treatment and outcome disparities between patients with private insurance and patients without insurance (self-pay). Results: There were 45, 928 patients identified. Among those, 25.1% (n=11, 556) were self-pay. Patients without insurance had shorter hospital and ICU lengths of stay compared to patients with insurance. Among patients who survived their injuries, patients with insurance were more likely to be discharged to a rehabilitation facility compared to those without insurance (40.7% vs 21.5%). After matching, patients lack of insurance was associated with 19% and 27% lower odds of receiving a cranial procedure and monitoring, respectively, compared to having private insurance (p<0.001). Uninsured status was associated with a 51% higher odds of in-hospital mortality (p<0.001). Conclusions: Uninsured patients with a significant TBI received fewer interventional procedures and were had greater odds of in-hospital mortality. Significance and Contributions to Injury and Violence Prevention Science: Even after creating a relatively homogeneous population by analyzing those with severe isolated brain injuries and using propensity score matching techniques, the disparity in treatment and outcomes persisted among those with and without insurance. These findings require a greater exploration regarding why these disparities exist and the potential role of health policy for ensuring equitable treatment.